Giving Voice to Women with Substance Use Disorder: Findings from Expressive Writing About Trauma - Nancy Jallo; Patricia A. Kinser; Michelle Eglovitch; Nicola Worcman; Parker Webster; Anika Alvanzo; Dace Svikis; Sarah Meshberg-Cohen (Women's Health Reports)
Background: Trauma exposure is a risk factor for substance use disorders (SUD) among women. This study explores written content from an expressive writing (EW) intervention conducted within a residential SUD program to examine themes across trauma experiences and characterize their deep insight into such experiences. Materials and Methods: This qualitative study is a secondary data analysis of written content of the first writing session from women (n = 44) randomized to an EW condition while in residential SUD treatment. Results: Nearly all participants (72.7% African American; mean age 37.3 years) reported a significant trauma event (93.2%) with an average of 3.7 types of trauma events (54.4% had a current posttraumatic stress disorder diagnosis). Four primary themes emerged: (1) trauma across the lifespan; (2) loss of safety; (3) altered self-concept; and (4) desire to move on. Most participants identified interpersonal trauma, especially at an early age, as well as parental neglect and physical and/or sexual violence. These themes indicate a pattern of interpersonal betrayal and paint a picture of trauma and the subsequent “rippling effect” such that the physical, mental, and emotional consequences were often as impactful as the event itself. However, there was also a desire to move on and gain a sense of normalcy. Conclusions: Findings highlight the importance of the written word and addressing underlying trauma in addiction treatment to facilitate healing and the woman's desire to move on.